Juan Formell, cronista del ingenio popular del cubano - Borges Bartutis, María Vicenta (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
The objective of this work is to pay tribute to the chronicler of the popular ingenuity of my beautiful Cuba, Juan Formell, one of the great and distinguished of Cuban popular music, the eternal conductor of the “Los Van Van” orchestra. In addition, it is intended to highlight the value of the lyrics of his compositions for the teaching and learning process of Spanish as a second language and culture; Today, through his songs, the amulet of Cuban popular music recreates experiences of different moments of the daily reality of the people. Serve this article as a tribute to this humble musician who gave the Cuban joy, rhythm, wisdom, spirituality and above all respect for identity.